Effects of topical negative pressure therapy on perfusion and microcirculation of human skin - Muenchow, S.; Horch, Raymund E.; Dragu, Adrian (Clinical Hemorheology and Microcirculation, 2019)
BACKGROUND: Topical negative pressure wound therapy (TNPWT) is one of the most frequently used techniques in wound treatment. But some of the underlying mechanisms still remain unclear. One possible explanation is an improved microcirculation by TNPWT.
CRIS-Team WoS Importer:2019-10-15